Dynamical links of convective storms associated with tropospheric biennial oscillation in the Indian monsoon regime - U. V. Murali Krishna; Subrata Kumar Das; K. N. Uma; Abhishek Kumar Jha; G. Pandithurai (Scientific Reports, 2022)
Abstract Tropospheric Biennial Oscillation (TBO) is characterized by a tendency for a relatively stronger monsoon to be followed by a relatively weaker one (positive) or vice-versa (negative). This study examines the distribution of different convective systems occurring during TBO phases over the Indian monsoon region. During negative TBO phase, convection is preferential over the Arabian Sea (AS), whereas during positive TBO phase, it is favoured over the land areas and Bay of Bengal (BoB). The isolated shallow convection (ISC) is dominated over the AS and Indian west coast during negative TBO years. A relatively stable environment (statically) capped with drier mid-troposphere results in abundant ISC over the AS. Broad stratiform rain (BSR) dominates over the central and east coast of India, BoB and Myanmar coast during positive TBO years and wide convective core (WCC) are present along the orographic regions, i.e., Myanmar coast and Western Ghats during negative TBO phase. The anomalous easterlies induced by the upper-ocean temperature gradient interact with the mean monsoon winds during positive TBO to provide pathways for developing BSR echoes. The deep-wide convection (DWC) are higher along the Himalayan foothills during positive TBO years. The moist low-level flow from the AS is trapped by dry mid-level flow from high latitudes, resulting in orographic lifting along the Himalayan foothills and form DWC.